2020
DOI: 10.5194/aab-63-145-2020
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in quantitative and qualitative sperm characteristics in fertile and subfertile stallions

Abstract: Abstract. Horses are seasonal breeders with a natural breeding season beginning in spring and extending through midsummer. In this study, quantitative and qualitative parameters of chilled stallion semen were compared between fertile and subfertile stallions and between the breeding and the non-breeding season. Semen quality parameters compared included ejaculate volume, sperm concentration, total sperm number, sperm morphology, and computer-assisted semen analysis (CASA)-derived sperm movement characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
6
2
0
Order By: Relevance
“…The sexual beheviour is the highest in summer and spring, however it is usually reduced in winter (Waheed et al, 2015). Additionally, sexual behavior, ejaculate volume, total sperm output and motility were found to be higher during summer and spring compared to winter (Suliman et al, 2020). These findings are matching with our finding reported that the number of mounts per ejaculation, reaction time, time to erection, ejaculation times and time to ejaculation were significantly lower in summer season compared with other seasons.…”
Section: Discussionsupporting
confidence: 90%
“…The sexual beheviour is the highest in summer and spring, however it is usually reduced in winter (Waheed et al, 2015). Additionally, sexual behavior, ejaculate volume, total sperm output and motility were found to be higher during summer and spring compared to winter (Suliman et al, 2020). These findings are matching with our finding reported that the number of mounts per ejaculation, reaction time, time to erection, ejaculation times and time to ejaculation were significantly lower in summer season compared with other seasons.…”
Section: Discussionsupporting
confidence: 90%
“…The ejaculate gel volume was not significantly different in the breeding season and the non-breeding season. This result is in agreement with Suliman et al (2020). While, Morel (2008) reported that the ejaculate gel volume was higher in the breeding season than non-breeding season.…”
Section: Microscopic Examination Of Stallion Fresh Semensupporting
confidence: 89%
“…While, Warnke et al (2001) reported that the motility of stallion sperm is higher in winter (non-breeding season) than in summer and spring (breeding season) Evaluation of sperm cell concentration showed that no significant difference between stallions in breeding season and non-breeding season. These data was in a harmony with the results reported by Suliman et al (2020). These data is not in agreement with results obtained by (Janett et al, 2003 andWach-Gygax et al, 2017) who reported that the sperm cell concentration of stallion ejaculate was lower in the summer (breeding season) than in winter (nonbreeding season).…”
Section: Microscopic Examination Of Stallion Fresh Semensupporting
confidence: 65%
“…There is also an absence of any knowledge on the time of insemination or any veterinary care that the mare is provided before or after insemination. Therefore, given that previous studies suggest sperm movement is significantly associated with fertility [ 18 , 19 , 20 ], we primarily focused this study on this attribute of semen quality.…”
Section: Introductionmentioning
confidence: 99%